2020
DOI: 10.3324/haematol.2020.253740
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells proliferation associated with acute myeloid leukemia: phenotype profile and mutation landscape

Abstract: Neoplasms involving plasmacytoid Dendritic Cells (pDCs) include Blastic pDC Neoplasms (BPDCN) and other pDC proliferations, where pDCs are associated with myeloid malignancies: most frequently Chronic MyeloMonocytic Leukemia (CMML) but also Acute Myeloid Leukemia (AML), hereafter named pDC-AML. We aimed to determine the reactive or neoplastic origin of pDCs in pDC-AML, and their link with the CD34+ blasts, monocytes or conventional DCs (cDCs) associated in the same sample, by phenotypic and molecular analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 44 publications
4
69
1
Order By: Relevance
“…The stable pattern in normal BM gives even more weight to the astonishing diversity disclosed in the seven cases analyzed here. Indeed, it could have been expected that the RUNX1 mut signature would be associated with PDC differentiation [6,7] but several intriguing facts may be noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stable pattern in normal BM gives even more weight to the astonishing diversity disclosed in the seven cases analyzed here. Indeed, it could have been expected that the RUNX1 mut signature would be associated with PDC differentiation [6,7] but several intriguing facts may be noted.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX1 mut AML is most often purely blastic by cytological assessment and myeloperoxidase-negative, corresponding to AML with minimal differentiation [2][3][4]. In some leukemias with RUNX1 mut , mixed-phenotype acute leukemia (MPAL) characteristics can, however, be present [5], and RUNX1 mut has also been associated with AML cases with a plasmacytoid dendritic cell (PDC) component [6,7]. However, RUNX1 mut has only seldom been reported in blastic PDC neoplasms (BPDCN) [6,8], while clusters of mature PDCs have been described in bone marrow (BM) biopsies from patients with MPN or MDS/MPN [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in acute myeloid leukemia (AML), Zalmai et al. identified a group of pDC-AML with completely different phenotype from BPDCN, with high expression of CD34 and CD303, low expression of CD123 and cTCL1, and no expression of CD56 ( 119 ). Molecular analysis indicated that these pDCs were inactive and neoplastic, and exhibited frequent RUNX1 mutations ( 119 ).…”
Section: Role Of Pdcs In Cancersmentioning
confidence: 99%
“…identified a group of pDC-AML with completely different phenotype from BPDCN, with high expression of CD34 and CD303, low expression of CD123 and cTCL1, and no expression of CD56 ( 119 ). Molecular analysis indicated that these pDCs were inactive and neoplastic, and exhibited frequent RUNX1 mutations ( 119 ). Moreover, studies showed that clinical use of tagraxofusp (SL-401) completely inhibited protein synthesis leading to cell death of pDCs, which had a positive effect on inhibiting acute transformation in leukemia ( 61 , 118 ).…”
Section: Role Of Pdcs In Cancersmentioning
confidence: 99%